(untitled) (Fiep Bulletin - online, 2011)
Amputation is a word derived from Latin that means the complete or partial removal of a limb of the body. After the amputation, the use of a prosthesis provides a normal body image, aiding the person to develop higher self esteem and physical abilities. The aim of the use of prosthesis is rehabilitate the patient to have a normal life and integrate this person to the society, enabling him to move with the use of the prosthesis. Due to the higher number of variables that can compose a functional evaluation, this study aims to identify the main variables to evaluate the march capacity with prosthesis and the functional independence for the transfemoral amputees. An epidemiologic study was accomplished at FAG’s Integrated Clinics, the sample was composed by 30 patients with transfemoral amputation, who contemplated the inclusion criteria. The questionnaire was applied in August of 2009, the instrument was composed by 23 questions, 2 subjective and 21 objective ones. Three dimensions were classified in the research as: dimension 1: march capacity with prosthesis, dimension 2: functional independence and dimension 3: socialization, and this instrument was composed by 11 items.